DEVELOPING ORAL COMMUNICATION SPEAKING SKILLS IN PRIMARY SCHOOL LEARNERS - Yuldasheva Muxlisa; Igamberdieva Shahnoza (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
It is often argued that spoken language in the learning process is a very important aspect of school education and pedagogy. Children, striving to discover and understand the world around them, constantly ask questions. Oral speech skills are a crucial factor for teacher-child interaction and the development of oral speech in children. In early education, the development of oral speech is especially important for interaction, social relations and friendship, as well as for the formation of a sense of belonging. Teachers help children better develop their oral language skills both directly through language interaction with them and indirectly by creating an environment rich in incentives for learning. Teachers' oral communication skills are able to actively support the implementation of the curriculum and the achievement of its goals.